Argon cold atmospheric plasma eradicates pathogens in vitro that are commonly associated with canine bacterial keratitis - Marx, Anne Helene; Oltmanns, Hilke; Meißner, Jessica; Verspohl, Jutta; Fuchsluger, Thomas; Busse, Claudia (Frontiers in Veterinary Science, 2024)
Objective:To investigate the antimicrobial effect of cold atmospheric plasma (CAP) on pathogens associated with canine bacterial keratitis. Material and methods: Pseudomonas aeruginosa, Staphylococcus pseudintermedius, and Streptococcus canis strains, which were obtained from dogs with infectious keratitis, were subjected to testing. For each species, four isolates and a reference strain were cultivated on Columbia sheep blood agar and treated with the kiNPen Vet® plasma pen from Neoplas GmbH, Greifswald, Germany. Various continuous treatment durations (0.5, 2, and 5 minutes) were applied, along with a 0.5-minute treatment repeated four times at short intervals. These treatments were conducted at distances of 3 and 18 mm between the agar surface and the pen. Results CAP treatment reduced bacterial growth in all three species. Results: The most effective treatment duration was 5 minutes at 3 mm distance, resulting in inhibition zones ranging from 19 -22 mm for P. aeruginosa, 26 -45 mm for S. pseudintermedius and an overall reduction of bacterial growth for Str. canis. Inhibition zones were smaller with decreasing treatment duration and larger distance. Treatment times of 30 seconds repeated four times and 2 minutes showed comparable results. Treatment with argon alone did not lead to visible reduction of bacterial growth. Conclusion: Argon cold atmospheric plasma demonstrated a potent in vitro antimicrobial effect on P. aeruginosa, S. pseudintermedius and Str. canis strains with the latter showing the highest sensitivity.